Interpersonal conflicts as a predictor of academic performance among secondary school students - Cherono, Abigael; Muriithi, Ciriaka Gitonga; Obura, Elizabeth Atieno (Institute of Advanced Engineering and Science, 2025)
There is a global concern about promoting peaceful coexistence in school learning environments. Interpersonal conflicts in schools can lead to academic difficulties and violent interactions among the students. The academic performance among students in Embu East Sub-County has not been satisfactory and has become an issue of concern. The study conducted a quantitative correlational study to determine the relationship between interpersonal conflicts and students’ academic performance. A correlational research design was used, involving a sample of 357 form 2 students sampled through simple random sampling. Data were collected using the interpersonal conflict questionnaire and document analysis. The items in the questionnaire yielded a Cronbach’s alpha coefficient value of 0.759. Data were analyzed using inferential statistics, including Pearson’s correlation and simple linear regression analysis. The findings revealed a weak negative and statistically significant relationship between interpersonal conflicts and academic performance among the students (β=-0.152**, p=0.008). The study concludes that interpersonal conflict engagement among students leads to poor academic performance. Therefore, schools should prioritize integrating programs that build interpersonal and social skills among students to improve interpersonal relationships and academic performance.